2021
DOI: 10.1021/acs.jced.0c01017
|View full text |Cite
|
Sign up to set email alerts
|

Thermophysical Properties of 1-Butyl-3-methylimidazolium tris(pentafluoroethyl)trifluorophosphate, [C4mim][(C2F5)3PF3], and of Its IoNanofluid with Multi-Walled Carbon Nanotubes

Abstract: Thermophysical properties of 1-butyl-3-methylimidazoliumtris-(pentafluoroethyl) trifluorophosphate, [C 4 mim][(C 2 F 5 ) 3 PF 3 ] (CAS RN 917762-91-5) ionic liquid, were measured in the temperature range T = (283.15−353.15) K, at P = 0.1 MPa. These properties include density, isobaric heat capacity, speed of sound, refractive index, viscosity, and thermal conductivity and their correlation as a function of temperature. Data obtained were compared with the available literature, whenever available. Comparison of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 81 publications
0
13
0
Order By: Relevance
“…The possible existence of ultrasonic absorption in the measurement of the speed of sound of ionic liquids with Anton Paar DSA 5000 sound velocity meter was analyzed due to the strong absorption in the low-frequency range (less than 10 MHz) discussed by Dzida et al 15 The experience in this laboratory with amphiphilic compounds in water has shown in fact that reproducibility between measurements could not be achieved at this frequency for such water mixtures. However, any sign of similar phenomena with ionic liquids was never noticed, for temperatures greater than 293 K. 8,10,16 Following the results obtained for [C 2 mim]-[CH 3 SO 3 ] by Musiał et al, 17 we have compared all of the deviations of the available experimental data form the correlations proposed by Bioucas et al 2 in Figure S7. This figure shows that there is a very good agreement with the data of Marium et al 18 (±1.5 m•s −1 ; ±0.06%), and those of Musiał et al 1717 deviate around −1.3 m•s −1 (−0.07%), within the mutual uncertainty of data.…”
Section: Methodsmentioning
confidence: 74%
See 1 more Smart Citation
“…The possible existence of ultrasonic absorption in the measurement of the speed of sound of ionic liquids with Anton Paar DSA 5000 sound velocity meter was analyzed due to the strong absorption in the low-frequency range (less than 10 MHz) discussed by Dzida et al 15 The experience in this laboratory with amphiphilic compounds in water has shown in fact that reproducibility between measurements could not be achieved at this frequency for such water mixtures. However, any sign of similar phenomena with ionic liquids was never noticed, for temperatures greater than 293 K. 8,10,16 Following the results obtained for [C 2 mim]-[CH 3 SO 3 ] by Musiał et al, 17 we have compared all of the deviations of the available experimental data form the correlations proposed by Bioucas et al 2 in Figure S7. This figure shows that there is a very good agreement with the data of Marium et al 18 (±1.5 m•s −1 ; ±0.06%), and those of Musiał et al 1717 deviate around −1.3 m•s −1 (−0.07%), within the mutual uncertainty of data.…”
Section: Methodsmentioning
confidence: 74%
“…Extrapolated water-free values for the viscosity of [C 2 mim]­[CH 3 SO 3 ] can be obtained with the general procedure applied before, ,,,,,, using the equation The values of η exp ( x w , T ) were fitted with a polynomial in the mole fraction of water, for each temperature, and the derivative could be calculated as a function x w , eq S1 and Table S10. In previous cases, the limiting value of this derivative was used, as the last water mole fraction measured was close to zero.…”
Section: Results and Discussionmentioning
confidence: 99%
“…An updated IL thermal conductivity database was compiled from existing data in the literature, ,,,,− the NIST ILThermo database, and the new data generated in this work. Two recent GCMs for the prediction of IL thermal conductivity published by Lazzús (GCM-1) and Soares et al (GCM-2), respectively, were extended to include new functional group parameters and tested against the updated database.…”
Section: Methodsmentioning
confidence: 99%
“…There is little literature on the influence of ultrasound treatment conditions on the microstructure as well as thermal and rheological properties of INFs. Most of the research in the field was carried out under constant sonication settings [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] . The notable exceptions were works of Wittmar et al [32] , [33] , who investigated rheological properties of INFs containing 0.5 wt% 95% anatase TiO 2 with average particle size 5 nm or 100% anatase TiO 2 with average particle size from 5 to 26.4 nm and 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide [Emim][NTf 2 ], 1-ethyl-3-methylimidazolium tetrafluoroborate [Emim][BF 4 ], 1-butyl-3-methylimidazolium tetrafluoroborate [Bmim][BF 4 ], or 1-hexyl-3-methylimidazolium tetrafluoroborate [Hmim][BF 4 ], prepared with various sonication times up to 4 h. They concluded that the rheological behavior of nanodispersions was complex and depended on the type of IL.…”
Section: Introductionmentioning
confidence: 99%